Planning Conservation Strategies of Guiana Dolphin Related to Canal Flow and Habitat Changes in the Estuarine Lagunar Complex of Cananéia - Godoy, Daniela Ferro de; Pavanato, Heloise; Andriolo, Artur (Frontiers in Conservation Science, 2022)
Anthropogenic activities have altered the structure and function of coastal and estuarine ecosystems, affecting the animals that occur in these areas. Predictive models are useful to evaluate the impact of anthropogenic features over species distributions. In this study, we used generalised linear models to assess the influence of Valo Grande canal on the occurrence of Guiana dolphins in the Estuarine Lagunar Complex of Cananéia. Data were collected between January 2012 and November 2014, during 3 fieldworks per season. The predictions indicated that the discharge of fresh water has a negative influence on the populations of dolphins. Thus, it is clear that the Guiana dolphins presented a heterogeneous distribution within the studied estuary, and the areas of higher concentration of individuals deserve greater attention during the elaboration of conservation strategies.